Short-term response of the Ca cycle of a montane forest in Ecuador to low experimental CaCl2 additions - Cumbicus Torres, N. (2013)
The tropical montane forests of the E Andean cordillera in Ecuador receive episodic Sahara-dust inputs particularly increasing Ca deposition. We added CaCl2 to isolate the effect of Ca deposition by Sahara dust to tropical montane forest from the simultaneously occurring pH effect. We examined components of the Ca cycle at four control plots and four plots with added Ca (2 x 5kg ha(-1) Ca annually as CaCl2) in a random arrangement. Between August 2007 and December 2009 (four applications of Ca), we determined Ca concentrations and fluxes in litter leachate, mineral soil solution (0.15 and 0.30 m depths), throughfall, and fine litterfall and Al concentrations and speciation in soil solutions. After 1 y of Ca addition, we assessed fine-root biomass, leaf area, and tree growth. Only < 3% of the applied Ca leached below the acid organic layer (pH 3.5-4.8). The added CaCl2 did not change electrical conductivity in the root zone after 2 y. In the second year of fertilization, Ca retention in the canopy of the Ca treatment tended to decrease relative to the control. After 2 y, 21% of the applied Ca was recycled to soil with throughfall and litterfall. One year after the first Ca addition, fine-root biomass had decreased significantly. Decreasing fine-root biomass might be attributed to a direct or an indirect beneficial effect of Ca on the soil decomposer community. Because of almost complete association of Al with dissolved organic matter and high free Ca2+ : Al3+ activity ratios in solution of all plots, Al toxicity was unlikely. We conclude that the added Ca was retained in the system and had beneficial effects on some plants.